Anyone got a clue?
x^2+3x-4y+5=2
6=x-2y
thanks
Generally, I don't post entire solutions as this is a homework help forum. I can't just do the whole problem for you, you won't learn as much. I'll help you get started:
We substitute x = 2y+6 into the first equation:
$\displaystyle (2y+6)^2 + 3(2y+6) - 4y + 5 = 2$.
Expand:
$\displaystyle (4y^2 + 24y + 36) + (6y + 18) - 4y + 5 = 2$
You should be able to simplify the above expression into a quadratic in terms of y. Hopefully you know how to solve quadratics. If you don't, you should review that before continuing on with the problem.